The Influence of Price, Product Quality, Brand Image on Purchasing Decisions, With Consumer Trust as a Variable Mediating - Syiffa Arrahma, Nur; bastaman, Aam (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to determine the effect of price, product quality, brand image on purchasing decisions for Tupperware consumers in Jakarta mediated by consumer trust. The primary data used is responses to the Buying Decision of Tupperware consumers in Jakarta Mediated by Consumer Trust regarding Price, Product Quality, and Brand Image which were obtained through distributing questionnaires. The research population is Tupperware consumers in Jakarta. A sample of 100 people is taken by convenience sampling. Data were analyzed using PLS-based SEM. The results showed that the product quality and brand image variables affected consumer trust, the consumer trust variable affected purchasing decisions, while the price, product quality and brand image variables had no effect on purchasing decisions and the price variable did not affect consumer trust and purchase decisions. In addition, it is proven that consumer trust can mediate the relationship between product quality and purchasing decisions, and consumer trust is also able to mediate the relationship between brand image and purchasing decisions. In contrast, consumer trust is not able to mediate price and purchasing decisions.